HOST-COUNTRY TRAITS, INTRA-FIRM TECHNOLOGY TRANSFER AND COMPETITIVE ADVANTAGE: A CONCEPTUAL STUDY - Fazal, Syed Ali; Wahab, Sazali Abdul (PEOPLE: International Journal of Social Sciences, 2015)
Technological innovations have emerged as crucially significant factor for sustaining market competition and achieving competitive advantage in the 21st century. The Multinational Corporations (MNCs) as celebrities of innovation play significant role in diffusing technological knowledge throughout firms both nationally and internationally. Although numerous studies exist on technology transfer the majority of existing literature addresses the issues related to inter-firm transfer of technology only while the area related to intra-firm transfer of technology has been largely underexposed; study of which is believed to be ideal for fruitful exploration of profitability in technology transfer projects. Using data from MNCs in Malaysia the current study for the very first time would attempt to empirically find the effect of host-country traits on the performance of technology transferred by the MNCs and its subsequent impact on competitive advantage. Findings of this study are expected to contribute both theoretically in the body of knowledge and also in terms of practical implication for policy makers and MNCs and hence enriching the existing literature simultaneously.